Toward a Theory of the World Wide Web Vernacular: The Case for Pet Cloning. - Howard, Robert Glenn (Journal of Folklore Research)
This article depicts that the genre of the vanity page in general and the pet vanity page in particular does exist on the World Wide Web. Due to the technologies that arose as a result of growing commercial interest in Web-based communication during the 1990s, that content has come to be associated with particular aesthetic features of personal Web pages. In the early 1990s, personal pages of computer hobbyists, programmers, engineers, and researchers dominated the nascent World Wide Web. The vernacular needs the institutional to render its distinction meaningful. The conscious professional choice to engage a folk or quasi-folk style in commercial rhetoric is evidence that the vernacular has emerged in the World Wide Web medium.